2012
DOI: 10.1111/j.1467-856x.2012.00527.x
|View full text |Cite
|
Sign up to set email alerts
|

A Micro-Level Analysis of Support in Britain for the War in Afghanistan

Abstract: The article conducts a detailed and robust analysis of the social and attitudinal underpinnings of general support for the war in Afghanistan. • The article contributes to scholarly understanding of public attitudes in Britain on foreign policy issues and to the wider literature on public opinion and war. • The findings underline the long-standing 'gender gap' in attitudes to war, with men more in favour. • Labour partisanship and political knowledge are directly related to support for the war, though there is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…Overall, the evidence shows that sociological variables and political attitudes had strong direct effects on approval of the war in Afghanistan. Some of these findings underline well-established insights from the wider public opinion and foreign policy literature, including the existence of a “gender gap” in relation to military interventions (Clarke et al 2009; Clements 2011; 2012). As in the wider British population, amongst ethnic minorities men were more supportive of military action in Afghanistan than women.…”
Section: Resultsmentioning
confidence: 53%
See 1 more Smart Citation
“…Overall, the evidence shows that sociological variables and political attitudes had strong direct effects on approval of the war in Afghanistan. Some of these findings underline well-established insights from the wider public opinion and foreign policy literature, including the existence of a “gender gap” in relation to military interventions (Clarke et al 2009; Clements 2011; 2012). As in the wider British population, amongst ethnic minorities men were more supportive of military action in Afghanistan than women.…”
Section: Resultsmentioning
confidence: 53%
“…Assessing the role of these influences is important as to “a large degree, ordinary citizens interpret politics through the lens of social groups” (Berinsky 2009, 129). It builds upon the few studies that have examined public attitudes toward recent military interventions (Clarke et al 2009; Clements 2011; 2012) in the wider British population. Particularly relevant to the issue of support for Britain's role in Afghanistan and the international war against terrorism, it builds on existing research into the perceptions and attitudes of Muslims (Field 2007; 2011; 2012).…”
Section: Introductionmentioning
confidence: 99%
“…In line with previous research (Clements, 2012, 2014; Johns and Davies, 2014; Reifler et al, 2014; Tessler and Nachtwey, 1998), we include additional controls covering age (under 30s as reference), gender (men as reference), education (1 – illiterate/incomplete primary, 2 – completed primary, 3 – completed secondary, 4 – university), and personal economic situation (1 – very bad, 2 – bad, 3 – good, 4 – very good). 2…”
Section: Independent Variablesmentioning
confidence: 99%
“…One obvious first avenue to explore is whether supporters of democracy differ in their views regarding the forceful removal from office of Bashar al-Assad from the opponents of democracy. An impressive earlier body of research, which focused on Western public opinion on international intervention (Clements, 2012(Clements, , 2014Davies and Johns, 2016;Falomir-Pichastor et al, 2012;Reifler et al, 2014), has already shown how attitudinal profiles can explain support for various types of foreign interventions. In the context of the burgeoning research on pro-democracy attitudes among Arab publics (Berger, 2019a;Tessler et al, 2012), there are only few examinations of how and whether this might correlate with views on international politics (Berger, 2019b;Ciftci and Tezcür, 2016;Spierings, 2014;Tessler and Nachtwey, 1998).…”
Section: Hypothesesmentioning
confidence: 99%